Analysis of Visual Media as Students' Learning Motivation In Class XII IPS Students Of SMA Negeri 2 Sungai Raya, Desa Kapur, District of Kubu Raya - Putri Puspitasari; Shalihhin Affandi; Syifa Nur Qolbiana; Uray Lia Wahyuni; Fikri Nizar Zulkifli; Jagad Aditya Dewantara; Nuraini Asriati; Putri Tipa Anasi; Diah Trismi Harjanti (Jurnal Kewarganegaraan, 2020)
Abstract Today the development of education is increasingly rapid, the world of education is now experiencing a turmoil in improving science and quality of education. The quality of education can be improved by changing the mindset used as a basis for the implementation of learning. This can be used as the development of learning media. However, in its development there are still many teachers who have not been able to develop effective and efficient learning media, especially for geography education. This study uses a type of meta-analysis research. Meta Analysis is a set of quantitative statistical methods because it uses the calculation of numbers and statistics for practical interests. Data collection is done by distributing questionnaires online through Google Form. Participants by filling out a questionnaire totaling 45 people consisting of class XII IPS 1, XII IPS 2, and XII IPS 3. Where each participant in the class totaling 15 people. The research questionnaire is filled out by each student based on experience that has been obtained from learning outcomes using visual media and does not use visual media and student learning motivation based on their respective opinions. Based on the results of the research that has been conducted, it can be concluded that visual media provides learning motivation to students with an average motivational questionnaire score of 72.4% with good categories. Keywords: Visual Learning Media, Learning Motivation